Sustainable management of non-native thistles on the Western Slope - Coyle, John B., author; Nissen, Scott, advisor; Meiman, Paul, advisor; Beck, George, committee member; Brummer, Joe, committee member (Colorado State University. Libraries, 2017)
The scope of this research is unique in that it encompasses all phases of the weed management process. From problem identification, to identifying and testing solutions, to implementing the solution in a real world environment. The environmental challenges present on Blue Creek Ranch as well as the necessity to manage the expectations of stakeholders made this a multifaceted and challenging project. Field observations of the invasive thistle problem present on Blue Creek Ranch were confirmed through an extensive GIS survey and subsequent geospatial analysis. From this analysis, the invasive thistle infestation on the ranch could be quantified and presented in easily understood maps. This information helped guide management efforts and provided a tool to help educate stakeholders. Once this information was collected, an experiment was devised to judge the impacts of potential treatments on the ranch. Typical infestations of musk thistle an invasive annual thistle, favor highly disturbed lands. However, encroachment into the otherwise healthy montane range is being observed on Colorado's Western Slope. Within the context of a grass fed cattle operation, such as the one on Blue Creek Ranch, this range loss can result in decreased productivity. With the problem identified, there is now a need to identify herbicide treatments that can eliminate the thistles impacts while preserving the lands high forage value. We hypothesize that using selective herbicides, coupled with minimum dose rates, will not impact the overall forage quality of the range or the overall species abundance. In fall of 2014, four post emergent herbicide treatments (2 rates of aminopyralid, picloram and aminocyclopyrachlor) were applied in a split-plot design. In 2015 cover data and above ground biomass were collected to evaluate any treatment effects. Additionally, the edible forage component of the collected biomass was sent for feed analysis. In 2016 only cover data was collected. Across all treatments musk thistle was significantly reduced compared to control with no significant differences found between herbicide treatments. In evaluating species abundance it was found that no herbicide treatment resulted in any significant reduction. Finally, the feed analysis found that while the aminocyclopyrachor treatment tended to reduce the feed values of forbs there is no significant reduction in the overall feed values when total biomass (grass + forbs) is taken into account. These results indicate that regardless of which of the tested herbicides were used, musk thistle can be effectively controlled while at the same time preserving forage quality and, ultimately, production. Finally, all of this information was compiled into a weed management plan that will be presented to the owner and managers of Blue Creek Ranch to guide future management efforts. A plan was devised to define the scope of the management effort, specific management efforts and future monitoring activities. This management plan represents the culmination of the research conducted on Blue Creek Ranch and will be revised and updated as progress is made and new challenges arise.